Radiological imaging of pulmonary cavitations in adult multidrug-resistance and extensively drug-resistance tuberculosis patients - Ginting, Justin; Dominika, Katharina Ellen; Sanjaya, Ardo; Gunadi, Julia Windi (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
Mycobacterium tuberculosis is a pathogen that causes the infectious disease tuberculosis. Based on its resistance, tuberculosis can be divided into Drug-susceptible Tuberculosis (DS-TB) and Drug-resistant Tuberculosis (DR-TB). MDR-TB is one type of DR-TB when M. tuberculosis complex strains unresponsive to rifampicin and isoniazid. Another type of DR-TB is XDR-TB, A strain of M. tuberculosis that was unresponsive to rifampicin, isoniazid, fluoroquinolones, and at least 1 drug from group A. Research on the comparison of lung cavities in DS-TB, MDR-TB, and XDR-TB is still limited, this literature review is intended to explore comparative studies of lung cavity radiography in adult MDR-TB and XDR-TB patients. This literature review uses secondary data from literature searches through PubMed and Google Scholar by searching for keywords such as